CC4 Ocular syphilis on the rise: a case series. (30th June 2016) - Wood, Clare; Wells, Jane; Jones, Nick; Sukthankar, Ashish
Abstract : Background: Ocular involvement of syphilis remains relatively rare, however our clinic has seen a recent flurry of cases with 13 new diagnoses in the last 2 years, compared with 11 seen in the proceeding 10 years. It can be difficult to diagnose with no pathognomonic signs and can affect any structure of the eye. Aim: To present a cluster of 13 new cases ocular syphilis diagnosed from 2013 until January 2016. Methods: A retrospective case review. Results: In conjunction with our tertiary eye hospital, our clinicsaw 13 patients diagnosed with ocular syphilis between July 2013 and January 2016. All 13 patients were male: 6heterosexual; 5 men who have sex with men (MSM) and 2 bisexual. 3 patients were HIV positive. Mean age 42 (range 22–75). Ocular involvement included uveitis (anterior, posterior and pan-), optic neuritis, papillitis and retinitis. Cases include both unilateral and bilateral symptoms. All were treated as per national guidelines for neurosyphilis with procaine penicillin plus probenecid, proceeded by oral steroids. The majority of these patients' symptoms resolved following treatment, however a few continue to have ongoing visual disturbances. Discussion: We present our 13 cases of ocular syphilis. They illustrate the diverse range of presentations of ocular syphilis and the importance of partnership between the GU clinic and specialist ophthalmology services.